Parameter optimization, characterization, and crystallization mechanisms underlying the synthesis of zeolite A using liquid crystal display waste glass and sandblasting waste as alternative raw materials. Issue 5 (October 2022) - Lee, Wei-Hao; Lin, Ya-Wen; Lin, Kae-Long
Abstract: This paper examines the synthesis of zeolite A via hydrothermal alkali fusion using liquid crystal display waste glass (LCDWG) and sandblasting waste (SB). The design of the experiments was determined using the Box-Behnken method in conjunction with response surface design. Three factors were shown to have a pronounced effect on synthesis outcomes: (i) Si/Al molar ratio, (ii) crystallization temperature, and (iii) crystallization period. Synthesis parameters were optimized in accordance with the crystallinity (%) of the zeolite. XRD results revealed that increasing the Si/Al ratio improved the crystallinity and phase purity of the synthesized zeolite A. Increasing the crystallization temperature altered the crystal type and enhanced crystal purity; however, excessive temperatures reduced crystallinity and led to decomposition of the zeolite A phase. SEM results revealed that the resulting zeolite A possessed a cubic structure. ANOVA revealed that the Si/Al molar ratio had the most profound effect on the synthesis of zeolite A, followed by crystallization duration and crystallization temperature. The fact that the R 2 value (0.95) was similar to the adjusted R 2 value (0.8736) confirmed the efficacy of the proposed polynomial model. A highly significant F-value of 11.75 confirmed that the proposed model could be used for design purposes. The excellent water adsorption/desorption performance of the proposed zeolite A (49.83 g/ m 2 ; meeting JIS A 1470 standards) indicates its suitability as a low-cost construction material for a variety of applications. The ultimate objective of this study was to overcome difficulties encountered in the disposal of industrial waste by converting LCDWG and SB into zeolite A. Graphical Abstract: ga1 Highlights: The LCDWG and SB were shown to be a feasible source of Al2 O3 and SiO2 for the synthesis of zeolite A. The DOE was determined using the BBD method in conjunction with response surface design. This paper proposes a feasible model describing the crystallization of zeolite A. Optimal zeolite A synthesis conditions included a Si/Al molar ratio of 2.0, temperature of 120°C, and synthesis time of 36 h.